2012
DOI: 10.1007/s13304-012-0178-8
|View full text |Cite
|
Sign up to set email alerts
|

External stenting of pancreaticojejunostomy anastomosis and pancreatic duct after pancreaticoduodenectomy

Abstract: Pancreatic fistula is a major cause of morbidity and mortality after pancreaticoduodenectomy. External drainage of pancreaticojejunostomy anastomosis with a stent is used to reduce the rate of pancreatic fistula. This study compares the rates of pancreatic fistula between external stent drainage versus no-stent drainage for pancreaticojejunal anastomosis following pancreaticoduodenectomy. A total of 53 patients undergoing pancreaticoduodenectomy for various benign and malignant pathologies were included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Finally, stents provide a low resistance pathway for the pancreatic secretions towards the jejunum, decreasing leak around the anastomosis. 7,40,41 PJ stents can be internal or external, and we have been using both techniques, according to surgeon preference. Internal stents have one end in the pancreatic duct and the other in the jejunum, and rely on peristalsis for migration into the bowel and expulsion; they may be fixed with a fast absorbable stitch to prevent early expulsion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, stents provide a low resistance pathway for the pancreatic secretions towards the jejunum, decreasing leak around the anastomosis. 7,40,41 PJ stents can be internal or external, and we have been using both techniques, according to surgeon preference. Internal stents have one end in the pancreatic duct and the other in the jejunum, and rely on peristalsis for migration into the bowel and expulsion; they may be fixed with a fast absorbable stitch to prevent early expulsion.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have proved its benefit, especially in high-risk patients, while others have shown no effect. 7,19,41,48,49 Part of the argument against using stents is the morbidity associated with plastic stents, including stent occlusion and migration, which can result in pancreatic duct obstruction and pancreatitis. 31,40,49 Another frequent concern with internal stents is stent retention, which can lead to recurrent pancreatitis, the formation of stones, pancreatic insufficiency, and strictures of the pancreatic duct or the anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…[23] However, not all reports have concluded that stents are effective in reducing POPF incidence and other complications. Kaman et al [24] concluded that external drainage stents do not reduce the incidence of POPF compared with not using stents, and a meta-analysis by Zhou et al [25] showed that internal drainage stents not only did not reduce the incidence of POPF but increased the risk of POPF in the soft pancreas. An RCT in 2018 suggested that there was no difference between internal and external drainage stents, regardless of immediate or long-term complications, [26] and that there was a lack of a uniform understanding of stent tube placement and indications in China.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies, including prospective randomized trials as well as meta-analyses, have shown that external pancreatic duct stents significantly decrease the rate of pancreatic fistula and shorten the length of hospital stay [6][7][8]. Paradoxically, several studies have shown that external pancreatic duct stents have no effect and may even increase the incidence of postoperative pancreatic fistula [9][10][11]. In a meta-analysis, Dong et al [12] observed that the use of an external pancreatic duct stent was associated with a significantly lower incidence of pancreatic fistula in patients at high risk for pancreatic fistula compared with an internal stent, but there was no definitive conclusion because of the low quality of the evidence [8].…”
Section: ]mentioning
confidence: 99%